DO THE CHARECTERISTICS OF TECHNOLOGY LEAD TO UNIVERSITY PATENTS BEING UNEXPLOITED? - Abdul Majid , Izaidin; Wan Omar, Wan Zaidi; Ismail, Kamariah (2008)
The role of universities in commercialising their patents has been studied extensively. Some universities have succeeded in commercialising their patents especially through the route of licensing to established companies or forming new spin-off companies. However, there are some university patents remained unexploited, which represent wastage to the universities. This paper discusses what are the features of some patented technologies that are not commercialised. A case study of a university in Scotland was used in this study. Ten patents which are not being exploited by the University were selected. The inventors of these technologies were interviewed in depth, using semistructured questionnaires. The interviews were recorded, transcribed and the data was analysed based on a case and cross case aided by Nvivo software. The findings show that the most significant reason why patents are not exploited is associated with the technologies themselves. The technologies were found to be at very early stage of development, thus established companies were wary of taking them to market. Lack of motivation among the inventors to see their inventions being exploited, lack of industry networking and marketing of the TTO and inventor are another important reason that led to the inventions unexploited. Studying why some university patents were not exploited will enhance the understanding of the process of commercialisation of university patents, which would help refine the decision making process of patenting. Understanding the characteristics of the university inventions that have high economic potential thus should seek patent protections would reduce the number of unexploited patents.